THE TEACHING OF INTEGRATED ENGLISH PRODUCTIVE SKILLS THROUGH DIGITAL STORYTELLING PROJECT IN THE PANDEMIC COVID-19 AT UNIVERSITY OF PALANGKA RAYA - Misrita, Misrita; Ludang, Yetrie; Irine, Angelika Dhea; Qalyubi, Imam (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2020)
This research is a digital storyteller compilation project with English-based Computer Information Technology (ICT) instruction to promote the teaching of integrated English productive skills during the Covid-19 Pandemic which was carried out in the Semester 1 Student Class of the Forestry Study Program, Faculty of Agriculture, Palangka Raya University in the Academic Year 2020/2021. The purpose of this research is to find solutions to improve integrated English productive skills in the form of writing and speaking skills through making short films using computer information technology. These productive skills are in accordance with those mandated in the Indonesian National Qualifications Framework (KKNI) Higher Education Curriculum which demands the responsibility of educators to present professional learning to produce quality graduates, and who are able to adapt to their environment, especially in the industrial era 4.0. during the covid-19 pandemic. The Higher Education Curriculum is an institutional mandate capable of producing graduates (learning outcomes) which include new literacy abilities including data literacy and technology literacy. This type of research is a project which consists of several stages, namely: (1) topic selection, (2) design, (3) development, (4) evaluation, and (5) publication. The results of this digital storytelling project can then be accessed at www.youtube.com. Digital storytelling projects are also believed to be able to: (a) make students feel happy during teaching, (b) increase student participation in the teaching process, (c) improve student writing skills, (d) improve student skills in describing places, procedures, and so on. others orally, and (e) improve students' ICT literacy skills.